FLOURISHING TOWARD INNOVATION: HOW AUTHENTIC LEADERSHIP AND WORKPLACE SPIRITUALITY SHAPE INNOVATIVE BEHAVIOR IN INDONESIAN MINING COMPANY - Anindita Keumalahayati Alkarisya; Putri Mega Desiana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The mining industry in Indonesia faces global challenges and demands for downstreaming. This condition causes the need to increase competitiveness through continuous innovation. Innovation in the organization stems from the existence of individual innovative work behavior, which can be influenced by leadership style and positive conditions in the work environment. This study aims to analyze the influence of authentic leadership and workplace spirituality on innovative work behavior, with employee flourishing as a mediating variable. This study uses a quantitative approach with a survey method of 151 employees at one of the mining companies in Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The results showed that workplace spirituality had the strongest influence on employee flourishing and innovative work behavior. Authentic leadership also has a significant effect on innovative work behavior and employee flourishing. Employee flourishing in this study was shown to play a mediating role in the relationship between workplace spirituality and innovative work behavior. However, no mediating role of employee flourishing was found in the relationship between authentic leadership and innovative work behavior. The results of this study reinforce the applicability of broaden-and-build and job-demands resources theories, which state that positive emotions and respectful relationships in organizations can build psychological resources that can support innovation.